Self-efficacy, religiosity and opinions on the role of religion in coping with the difficulties of medical students - Joanna Żołnierz; Katarzyna Wac; Agnieszka Brzozowska; Jarosław Sak (Kazimierz Wielki University, 2017)
Aim: The aim of the thesis was determining the relationship between self-efficacy, styles of religious coping and opinions of the students of medicine on the role of religion in dealing with difficulties. Method: The participants of the study were 273 students of medical sciences aged between 19 and 27. The study was being conducted from November 2015 to February 2017. The method employed was General Self-Efficacy Scale (GSES), Brief COPE scale and a self-devised questionnaire. Results: The level of self-efficacy was remarkably higher among men than among women (p=0,000006), as well as among students from cities (p=3,003) and was connected with economic circumstances of respondents. Any significant dependence between self-efficacy and positive and negative religious coping was not observed neither among the whole group of students, a group of Catholics, a group of non-believers, or a group of non-Christians, (p>0,05). A significant relationship between assessment of the impact of religion on dealing with difficulties and positive religious coping was observed in the scale Brief RCOPE in the whole group, and in the group of only Chatolics. (R=0,62 vs. R=0,63). The statistical analysis indicated a remarkable relationship between assessment of the impact of religion on dealing with difficulties and positive (R=0,42) and negative religious coping (R=0,29) in the group of non-believers and in the group of members of other religious denominations. Conclusion: The survey research show that in the group of Catholics, the greater belief in positive influence of religion on dealing with problems, the more frequent is engaging in positive strategies of religious coping. On the other hand, in the group of non-believers and members of other religious denominations greater belief in the impact of religion on positive dealing with difficulties entails frequent employing of both positive, as well as negative strategies of religious coping.